2020
DOI: 10.1093/inthealth/ihaa099
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid patterns of anaemia and diarrhoea among children aged under 5 years in Ghana: a multivariate complex sample logistic regression analysis and spatial mapping visualisation

Abstract: Background Anaemia and diarrhoea are known independent causes of under-five morbidity and mortality. This study sought to investigate predictors of comorbid patterns of anaemia and diarrhoea using the 2014 Ghana Demographic and Health Survey (GDHS). Methods The study employed analysis of secondary data from the 2014 GDHS. We performed a multivariate complex sample logistic regression and spatial analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 27 publications
4
20
0
2
Order By: Relevance
“…Floors made of unimproved materials can serve as breeding grounds for disease-causing agents [ 25 ]. However, a study by Duah et al [ 1 ], showed no significant association between the main floor material and comordity among CU5 in Ghana. Though diarrhoea is a common variable in this study and that of Duah et al [ 1 ], the difference in the findings may be attributed to the latter study’s use of anaemia which is more related to nutritional defficiency compared to the use of ARI which is a respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Floors made of unimproved materials can serve as breeding grounds for disease-causing agents [ 25 ]. However, a study by Duah et al [ 1 ], showed no significant association between the main floor material and comordity among CU5 in Ghana. Though diarrhoea is a common variable in this study and that of Duah et al [ 1 ], the difference in the findings may be attributed to the latter study’s use of anaemia which is more related to nutritional defficiency compared to the use of ARI which is a respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Duah et al [ 1 ], showed no significant association between the main floor material and comordity among CU5 in Ghana. Though diarrhoea is a common variable in this study and that of Duah et al [ 1 ], the difference in the findings may be attributed to the latter study’s use of anaemia which is more related to nutritional defficiency compared to the use of ARI which is a respiratory disease. In spite of this, our finding of an association with the type of floor material and comorbid condition plausibly suggests the vulnerability of CU5 to disease-causing organisms which may be found on surfaces of unimproved floor materials they have regular contact with.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Anemia ini sering ditemukan pada saat aktivasi kekebalan sedang berlangsung pada berbagai gangguan termasuk infeksi, keganasan, autoimunitas, dan penyakit graftversus-host. 24 Anak dapat mengalami anemia bersamaan dengan diare diduga karena sitokin inflamasi seperti TNF-α dan IL-6, yang meningkat pada diare, juga terlibat dalam jalur inflamasi pada anemia penyakit kronis 25 .…”
Section: Hubungan Kadar Hemoglobin Dengan Lama Rawat Inap Pada Balita...unclassified